A Conversion-Period Cemetery at Woodlands, Adwick-le-Street, South Yorkshire*. (1st January 2016) - McKinley, Jacqueline I.
Abstract : Excavations by Archaeological Research and Consultancy University of Sheffield in 2007–8 revealed the remains of an Anglo-Saxon inhumation cemetery at North Ridge Community School, Woodlands, Doncaster. Forty graves were excavated, thirty-seven of which contained in situ burial remains. Radiocarbon samples from five graves gave an overall date range extending from the late seventh to late eight centuries AD. The latter is commensurate with that suggested by the limited range of grave goods recovered from two of the graves. The majority of the burials were made supine and extended within graves predominantly arranged in two rows, and the demographic profile suggests it served a domestic population. There were occasional deviations from the 'norm' in burial position and orientation, and one adult female appears to have suffered a violent death. Strontium and Oxygen (Sr/O) isotope analysis of seven individuals showed mixed origins including local, regional/national migrants and two long-distance migrants.